The H5N1 influenza virus in Indonesia has caused more than 100 people died due to the virus infections. Cases in humans were mostly due to the virus spread from the infected birds. This study characterized molecularly the H5N1 virus from birds around the H5N1 infection cases in humans in Indonesia. Result from this study revealed that in several cases, waterfowl species could become the source of H5N1 infections in human. We found that the one of six viruses used in this study probably was a fi - NI LUH PUTU INDI DHARMAYANTI; FERA IBRAHIM; . DARMINTO; AMIN SOEBANDRIO (Bogor Agricultural University, Indonesia, 2011)
The H5N1 influenza virus in Indonesia has caused more than 100 people died due to the virus infections. Cases in humans were mostly due to the virus spread from the infected birds. This study characterized molecularly the H5N1 virus from birds around the H5N1 infection cases in humans in Indonesia. Result from this study revealed that in several cases, waterfowl species could become the source of H5N1 infections in human. We found that the one of six viruses used in this study probably was a first antigenic shift virus in Indonesia. This study shows that the AI viruses isolated from birds around humans infected by H5N1 virus has specific characteristics namely the presence of several amino acid substitutions especially on the M1 and M2 proteins. The substitutions are similar in most of H5N1 human cases in Indonesia.